The societal context of professional practice: Examining the impact of politics and economics on journalistic role performance across 37 countries (2024)
The impact of socio-political variables on journalism is an ongoing concern of comparative research on media systems and professional cultures. However, they have rarely been studied systematically across diverse cases, particularly outside Western democracies, and existing studies that compare western and non-western contexts have mainly focused on journalistic role conceptions rather than actual journalistic practice. Using journalistic role performance as a theoretical and methodological framework, this paper overcomes these shortcomings through a content analysis of 148,474 news stories from 365 print, online, TV, and radio outlets in 37 countries. We consider two fundamental system-level variables—liberal democracy and market orientation—testing a series of hypotheses concerning their influence on the interventionist, watchdog, loyal-facilitator, service, infotainment, and civic roles in the news globally. Findings confirm the widely asserted hypothesis that liberal democracy is associated with the performance of public-service oriented roles. Claims that market orientation reinforces critical and civic-oriented journalism show more mixed results and give some support to the argument that there are forms of “market authoritarianism” associated with loyalist journalism. The findings also show that the interventionist and infotainment roles are not significantly associated with the standard measures of political and economic structure, suggesting the need for more research on their varying forms across societies and the kinds of system-level factors that might explain them.